2019
DOI: 10.1159/000500227
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Recombinant Human Acetylcholinesterase Activity by Antipsychotics

Abstract: Background/Aims: Extrapyramidal symptoms (EPS) are representative side effects of antipsychotics, caused by their inhibitory action on dopaminergic nerves in nigrostriatal pathways. EPS could be also caused by direct augmentation of cholinergic effects, for example, by acetylcholinesterase (AChE) inhibition. We investigated the potential inhibitory effects of 26 clinically available antipsychotics on the activity of recombinant human AChE (rhAChE) to predict the role of antipsychotic-induced AChE inhibition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Inhibitory Actions of Antidepressants, Hypnotics, and Anxiolytics on rhAChE Activity rhAChE activity was measured using a plate reader (Infinite ® F200 PRO; Tecan, Männedorf, Switzerland) as previously described. 3) Briefly, rhAChE (C1682; Sigma-Aldrich Co., LLC, St. Louis, MO, U.S.A.) was dissolved in 0.1 M PB (0.1 mg/mL) and then diluted 200-fold with modified Hanks' Balanced Salt Solution (HBSS) of the following composition (in mM): NaCl, 136.9; KCl, 5.37; CaCl 2 , 1.26; MgCl 2 , 0.81; Na 2 HPO 4 , 0.77; KH 2 PO 4 , 0.44; NaHCO 3 , 4.17; and glucose, 5.55. The diluted solution (50 µL) and 5 mM DTNB (149 µL) were added to each well of a 96-well plate and incubated for 10 min at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory Actions of Antidepressants, Hypnotics, and Anxiolytics on rhAChE Activity rhAChE activity was measured using a plate reader (Infinite ® F200 PRO; Tecan, Männedorf, Switzerland) as previously described. 3) Briefly, rhAChE (C1682; Sigma-Aldrich Co., LLC, St. Louis, MO, U.S.A.) was dissolved in 0.1 M PB (0.1 mg/mL) and then diluted 200-fold with modified Hanks' Balanced Salt Solution (HBSS) of the following composition (in mM): NaCl, 136.9; KCl, 5.37; CaCl 2 , 1.26; MgCl 2 , 0.81; Na 2 HPO 4 , 0.77; KH 2 PO 4 , 0.44; NaHCO 3 , 4.17; and glucose, 5.55. The diluted solution (50 µL) and 5 mM DTNB (149 µL) were added to each well of a 96-well plate and incubated for 10 min at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we evaluated the inhibitory actions of 26 clinically available antipsychotics on recombinant human AChE (rhAChE) and found that aripiprazole may inhibit AChE within its clinically achievable blood concentration range (CABCR). 3) Other than antipsychotics, some psychotropic drugs used for BPSD have also been reported to inhibit AChE, [4][5][6][7][8][9] but the AChE inhibitory actions of all clinically available psychotropic drugs have not been fully tested. In this study, we tested the potential inhibitory effects of 31 antidepressants, 21 hypnotics, and 12 anxiolytics on rhAChE activity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of DMSO and acetone on rhAChE activity were assessed as previously described. 7) Briefly, rhAChE (50 µL, 0.025 µg/well) and 5 mM 5,5′-dithio-bis-(2-nitrobenzoic acid) (DTNB, 140 µL) were added to each well of a 96-well plate and incubated for 10 min at 30 °C. Subsequently, 10-100% DMSO or acetone (10 µL) was added to the corresponding wells and incubated for 30 min at 30 °C.…”
Section: Assessment Of Effects Of Dmso and Acetone On Achand Carbacho...mentioning
confidence: 99%
“…6) AChE inhibition (%) was calculated using GraphPad Prism™, as previously described. 7) All values are presented as the mean ± standard error of the mean (S.E.M.) for different numbers (n) of experiments.…”
Section: Assessment Of Effects Of Dmso and Acetone On Achand Carbacho...mentioning
confidence: 99%
“…Brexpiprazole has less partial agonism at the D2R relative to aripiprazole but has higher 5-HT2A antagonism which may explain its lower likelihood of inducing DIMD. Aripiprazole’s higher potency in inhibiting acetylcholinesterase activity may also play a role in its propensity to cause more DIMD relative to brexpiprazole [ 8 ]. It was approved for use in schizophrenia and as adjunctive treatment of depression in 2015 [ 9 ].…”
Section: Incidence Of Dimd With Novel Antipsychoticsmentioning
confidence: 99%